Stress of Anesthesia Personnel at Srinagarind Hospital during Covid-19 Pandemic - Aimnang, Charinee; Tribuddharat, Sirirat; Sathitkarnmanee, Thepakorn; Sabangban, Lamyai (Srinagarind Medical Journal, 2021)
Background and Objective: The outbreak of Covid-19 has caused stress to medical personnel who dealed with the patients. The objective of this study was to evaluate the level of stress and related factors in anesthesiologists and nurse anesthetists. Methods: This was a prospective descriptive study in anesthesiologists and nurse anesthetists working at Srinagarind Hospital, Khon Kaen University between August and September 2020 with purposive sampling using a questionnaire consisted of Suanprung Stress Test-20 (SPST-20) with related factors. Results: A total of 72 samples were recruited. The overall stress level was moderate with mean SPST-20 score of 2.56 ± 1.34. The main related factors were: complicated working protocol; expertise requirement; people contact; definite criteria for job promotion; and inadequate rest area. Conclusions: Under the Covid-19 pandemic, the stress level of anesthetic personnel at Srinagarind Hospital was moderate. The related factors in 5 categories were identified for developing interventions to reduce stress in the next pandemic.